2020
DOI: 10.5585/remark.v19i4.16122
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Interno em cooperativa de crédito do Brasil

Abstract: Objetivo: O objetivo é analisar determinadas iniciativas de Marketing Interno de uma cooperativa de crédito brasileira, na visão dos seus colaboradores.Método: Foi aplicada pesquisa quantitativa (911 indivíduos), de caráter descritivo, com uso de modelagem de equações estruturais e de corte transversal, com instrumento baseado em Dessler (1996), Lings e Greenley (2005) e Shekary et al. (2012).Originalidade/Relevância: O estudo de aspectos específicos do Marketing Interno, a saber a comunicação, a liderança e o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some authors have argued for a long time that the role of the marketing management function should be to initiate, negotiate, and manage the exchange relations between the internal and external components of society. Scharf et al (2020) conducted research, whose results showed that internal communication effectively contributes to organizational goals and that the process of communicating with and leading people is a key factor in achieving those goals. However, if a company uses information technology systems acquired to facilitate the organization's communication process, they have a negative impact on internal communication and its goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors have argued for a long time that the role of the marketing management function should be to initiate, negotiate, and manage the exchange relations between the internal and external components of society. Scharf et al (2020) conducted research, whose results showed that internal communication effectively contributes to organizational goals and that the process of communicating with and leading people is a key factor in achieving those goals. However, if a company uses information technology systems acquired to facilitate the organization's communication process, they have a negative impact on internal communication and its goals.…”
Section: Literature Reviewmentioning
confidence: 99%